Why are women more food insecure than men? Exploring socio-economic drivers and the role of COVID-19 in widening the global gender gap - Mane, Erdgin; Giaquinto, Annarita Macchioni; Cafiero, Carlo; Viviani, Sara; Anriquez, Gustavo (Food and Agriculture Organization of the United Nations, 2023)
Women are more food insecure than men globally and in every region. This paper investigates the global gender gap in food insecurity and its evolution following the COVID-19 pandemic. Using the food insecurity experience scale (FIES) data collected from over 700,000 individuals across 121 countries, our empirical analysis showed that individuals aged 25– 34, regardless of gender, and women in rural areas had been disproportionally affected by the pandemic. Our analysis also confirmed that intersectional inequalities played a crucial role, with individuals in the age groups of 15–24 and 65+ being more food secure, while females aged 25–34 were more food secure than those aged 35–64. The differences by sex, residence, and age were significant even after controlling for income, education, employment, marital status, and household composition, indicating that other unobserved factors, including gender norms and discrimination, continue to hinder women’s food security. The econometric model allowed us to estimate the food security elasticity to income, which we then used to simulate the potential gains in food security if we eliminate the gender gaps in farm productivity and wages in agri-food systems. Finally, using coarsened exact matching (CEM) and entropy balancing (EB) matching techniques, we estimated that at least 57% of the current gap in food insecurity between women and men would be reduced by eliminating gender gaps in education, labor force participation, and income. Our results highlight the persistence of gender disparity in food security and offer evidence-based policy recommendations to support SDG 2.